Trasformasi Digital dan Kebutuhan Reskilling BUMN: Analisis Program Reskilling dan Upskilling dalam Menghadapi Disrupsi Digital: Studi Kasus BRI di Medan - Tioma Theresia Tp Bolon; Lastri Octaviani Girsang; Nara Pangihutan Saragih; Dea Riskylina Simamora; Aprinawati Aprinawati; Wisnu Rayhan Adhitya (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Digital transformation has become a necessity for State-Owned Enterprises (BUMN), particularly BRI, to face disruptions in the technological era. This study evaluates the reskilling and upskilling programs at BRI Medan in addressing the need for digital competencies, productivity improvement, and digital banking services. A mixed-method approach was used through in-depth interviews and questionnaires with program participants and HR management at BRI Medan, supported by digital policy documents and performance reports. The analysis focused on digital competencies, participant satisfaction, team performance impact, and regional implementation scale. Initial results indicate that the program emphasizes digital literacy, cybersecurity, the use of digital platforms, basic data analytics, and digital customer service. There was an improvement in skills and adaptability despite challenges such as limited training resources, varying employee profiles, and the need for job-specific customization. Positive impacts on operational efficiency and digital customer satisfaction were identified, with the acceleration of data-driven initiatives. The discussion highlights sustainable design, routine monitoring and evaluation, and the integration of the program into career paths. Policy implications: expansion of the program at Medan branches with a clear budget and strengthening the digital learning ecosystem. This study provides a practical overview of how BUMN, particularly BRI Medan, manages digital transformation through regional competency development.